2017
DOI: 10.1002/bmc.3903
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of l‐tetrahydropalmatine and its active metabolites in rat plasma by a sensitive ultra‐high‐performance liquid chromatography with tandem mass spectrometry method and its application in a pharmacokinetic study

Abstract: A sensitive and reliable ultra high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS) method was developed and validated for simultaneous determination of L-tetrahydropalmatine (L-THP) and its active metabolites L-isocorypalmine (L-ICP) and L-corydalmine (L-CD) in rat plasma,. The analytes were extracted by liquid-liquid extraction and separated on a Bonshell ASB C18 column (2.1 mm×100 mm; 2.7 μm; Agela) using acetonitrile-formic acid aqueous as mobile phase at a flow rate of 0.2 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…THP has four monodesmethyl metabolites: L-isocorypalmine, L-corypalmine, L-tetrahydropalmatrubine, and L-corydalmine ( Abdallah et al, 2017 ). The mean time to peak concentration (T max ) and half-life (T 1/2 ) of THP in rats were 0.44 and 4.49 h, respectively ( Wang W. et al, 2017 ), whereas those of healthy cocaine-using adults were 1.5 and 13.3 h, respectively ( Hassan et al, 2017 ). THP is only partially converted into metabolites, and the prototype drug remains in the blood ( Wang W. et al, 2017 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…THP has four monodesmethyl metabolites: L-isocorypalmine, L-corypalmine, L-tetrahydropalmatrubine, and L-corydalmine ( Abdallah et al, 2017 ). The mean time to peak concentration (T max ) and half-life (T 1/2 ) of THP in rats were 0.44 and 4.49 h, respectively ( Wang W. et al, 2017 ), whereas those of healthy cocaine-using adults were 1.5 and 13.3 h, respectively ( Hassan et al, 2017 ). THP is only partially converted into metabolites, and the prototype drug remains in the blood ( Wang W. et al, 2017 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…The mean time to peak concentration (T max ) and half-life (T 1/2 ) of THP in rats were 0.44 and 4.49 h, respectively ( Wang W. et al, 2017 ), whereas those of healthy cocaine-using adults were 1.5 and 13.3 h, respectively ( Hassan et al, 2017 ). THP is only partially converted into metabolites, and the prototype drug remains in the blood ( Wang W. et al, 2017 ). THP and its metabolites show high blood-brain barrier (BBB) permeability because of their high lipophilic properties ( Wang et al, 2012 ; Abdallah et al, 2017 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…A study by Xiaohong Xia et al found that L-THP achieved the effect of inhibiting BCa proliferation by blocking the cell cycle and promoting ERα degradation [ 9 ]. And Rotundine has been shown to have good results in clinical trials for the treatment of addiction [ 10 , 11 ]. Although rotundine has been studied for its anti-cancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…l ‐Tetrahydropalmatine ( l ‐THP) also known as rotundine, is a biologically active ingredient isolated from a traditional Chinese herb Rhizoma Corydalis‐yanhusuo (Gao, Hu, Zhang, Li, & Lin, 2014). Structurally, it resembles two DA molecules fused into a tetracyclic alkaloid (Mantsch et al, 2007; Wang et al, 2017b). Earlier research reported that l ‐THP can effectively treat cocaine addiction, The pharmacological profile of l ‐THP includes antagonism of D1 and D2 receptors as well as action at D3, α ‐adrenergic and serotonin receptors (Lee, Liu, Zhang, Huang, & Liu‐Chen, 2017; Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%